Group Counseling with Self-Instruction and Cognitive Restructuring Techniques to Improve Career Decision-Making Self-Efficacy - Ayuningtyas, Ira Palupi Inayah; Wibowo, Mungin Eddy; Purwanto, Edy (Jurnal Bimbingan Konseling, 2020)
This study aimed to examine the effectiveness of group counseling with self-instruction and cognitive restructuring techniques to improve career decision making self-efficacy of the Twelfth Grade (Class XII) students of Public Senior High School 1 Brebes (SMA Negeri 1 Brebes). The method used to this study was an experimental method with the experimental design of randomized pre-test post-test comparison group. For more, the collected data were analyzed by using one way ANOVA. The results showed that group counseling with cognitive restructuring technique, self-instruction technique, and the combination of both techniques was effective to improve career decision making self-efficacy. Further, the group counseling with self-instruction and cognitive restructuring techniques was more effective to improve career decision making self-efficacy compared to the counseling which used one technique only. Therefore, this study can give considerations to the possibility of using self-instruction and cognitive restructuring techniques as an intervention to improve the career decision making self-efficacy of SMA students.